Dietary Streptococcus thermophilus Probiotic Improves Growth of Pacific White Shrimp and Nile Tilapia - Dedi Fazriansyah Putra; Chintia Ariesti Pangestu; Rahma Enina Br Manik; Muhammad Nasir; Suratno Suratno; Elzein Muhammad Fahal (Jurnal Biodjati, 2026)
The intensive culture of Pacific white shrimp (Litopenaeus vannamei) and Nile tilapia (Oreochromis niloticus) is constrained by high feed costs, underscoring the need for strategies that enhance growth and feed efficiency without compromising environmental quality. Probiotics are increasingly proposed as functional feed additives, yet the performance of Streptococcus thermophilus in these two key tropical species remains poorly documented. This study evaluated the effects of graded dietary levels of S. thermophilus on growth performance, feed utilization, survival, and water quality in shrimp and Nile tilapia reared under controlled hatchery conditions. Shrimp (PL‑15) and Nile tilapia juveniles (4–6 cm) were cultured separately in 25‑L plastic tanks (effective water volume 15–16 L), at densities of 50 shrimp tank⁻¹ (31–32 ppt) and 15 tilapia tank⁻¹ (10–15 ppt), respectively, for 40 days. A completely randomized design with five treatments (0, 5, 10, 15, and 20 mL S. thermophilus/kg feed) and three replicates per treatment was used, with isoproteic diets based on fish meal and plant ingredients. Growth parameters (absolute weight and length gain, specific growth rate), feed conversion ratio, feed efficiency, survival, and basic water quality variables were measured and analyzed by one‑way ANOVA followed by Duncan’s test. Dietary S. thermophilus significantly enhanced absolute weight gain and specific growth rate in both shrimp and tilapia, while absolute length gain remained unchanged (P > 0.05). The 15 mL/kg treatment produced the best overall performance, with shrimp and tilapia reaching the highest weight gain, lowest feed conversion ratios (1.26 and 1.20, respectively), and feed efficiencies above 79%, whereas survival exceeded 70% in all probiotic groups and reached 100% in some tilapia treatments. Water quality, including dissolved oxygen, temperature, and pH, remained within recommended ranges, and probiotic pH (2–4) reflected active lactic acid fermentation without detrimental effects on rearing conditions. These findings demonstrate that dietary S. thermophilus at 10–15 mL/kg is an effective strategy to improve growth and feed utilization in shrimp–tilapia systems while maintaining suitable water quality, offering a practical approach to reduce feed-related production costs in sustainable tropical aquaculture.